Sistem Pendukung Keputusan Pemilihan Pembawa Acara Berita Terbaik Menerapkan Metode OCRA - Naomi Titania L.Toruan (Bulletin of Computer Science Research, 2021)
The selection process of the news presenter is still subjective where the assessment may not be based on criteria that have been set or without an objective look so that the selection process is done less precisely and the decision is are produced less satisfactory for prospective news hosts. In this study, authors used a decision support system with the OCRA method to find the value of weights and criteria, and to search for the final value or to find the value of the best news show carrier. Thus, the decision support system is needed to help the TVRI Medan in determining the best news host. Addressing the problem, it is necessary to build the application of the decision support system for the selection of the best news presenter by using OCRA method so that it can help and facilitate the TVRI Medan in decision making choose The best news presenter with a satisfactory decision